Use of the Potential Ecological Risk Index for Sediment Quality Assessment: A Case Study of Dam Lakes in the Thrace Part of the Marmara Region - Cem Tokatlı (Aquatic Sciences and Engineering)
Ergene River Basin, which is known as a critically contaminated habitat, is located in the Thrace Part of the Marmara Region of Turkey. Altınyazı, Karaidemir, Kayalıköy, Kırklareli, Sultanköy and Süloğlu Dam Lakes are located in the Ergene River Basin in the Thrace Region, which has very large agricultural lands because of rich soil and many freshwater resources. They were constructed by DSİ (State Water Works) in order to provide irrigation and drinking water and flood protection. The aim of this study was to evaluate the sediment quality of these artificial lentic ecosystems by investigating a total of 25 essential and toxic element accumulations and evaluate the ecological risks of toxic metals on the reservoirs by using Potential Ecological Risk Index (RI). Sediment samples were collected in the spring season (rainy) of 2018 from 15 stations and element concentrations were investigated by using an ICP-MS. According to the results of RI, cadmium, lead and arsenic were found to be the highest ecological risk factors for the basin reservoirs.